Developments in Strontium-Doped Calcium Phosphate Composite Scaffolds for Dental Applications and Bone Tissue Engineering - Khan Ahmadi, Faezeh; Mikeladze, Ketevan (Journal of Composites and Compounds, 2025)
This review article investigates the potential of strontium-doped calcium phosphate (Sr / CaP) composite scaffolds in the field of bone tissue engineering. Sr / CaP scaffolds play an effective role in improving bone regeneration and repair by stimulating bone cell growth, increasing osteoblast cell activity, and inhibiting osteoclast cell function. However, there are significant challenges in providing desirable mechanical properties as well as high biocompatibility, which require precise surface improvements and modifications of the scaffolds to achieve optimal performance. The main goal of this research is to improve the quality of the bond between the scaffold and bone tissue and facilitate the process of bone repair and regeneration. The results of this research can help develop new and practical solutions in the clinical treatment of bone defects and open new horizons in the design of bioimplants for bone tissue engineering.